Cooking with Fresh Herbs - Emily Minton; Martha Maddox (EDIS)
FCS8932, a 6-page illustrated fact sheet by Emily Minton and Martha Maddox, provides tips for washing, storing, and cooking with herbs — with recipes for herb blends and for dishes using fresh herbs. Includes references. Published by the UF Department of Family, Youth and Community Sciences, November 2010.